2016
DOI: 10.1038/srep22604
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Checkable Electrical Post-Treatment Method for Organic Photovoltaic Devices

Abstract: Post-treatment processes improve the performance of organic photovoltaic devices by changing the microscopic morphology and configuration of the vertical phase separation in the active layer. Thermal annealing and solvent vapor (or chemical) treatment processes have been extensively used to improve the performance of bulk-heterojunction (BHJ) organic photovoltaic (OPV) devices. In this work we introduce a new post-treatment process which we apply only electrical voltage to the BHJ-OPV devices. We used the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The performance of OEDs can be optimized in many ways, for example, by changing the volume composition of the active layer [ 19 , 20 ]. Different methods include the annealing process [ 21 , 22 , 23 ] or the use of different solvents [ 24 ]. Another method of improving the efficiency is the extraction/injection of electron layers and/or holes in the area of their contact with the organic semiconductor [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of OEDs can be optimized in many ways, for example, by changing the volume composition of the active layer [ 19 , 20 ]. Different methods include the annealing process [ 21 , 22 , 23 ] or the use of different solvents [ 24 ]. Another method of improving the efficiency is the extraction/injection of electron layers and/or holes in the area of their contact with the organic semiconductor [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum reported values of power conversion efficiency of these cells range from 5% to 16–18% [ 31 , 32 , 33 ]. Cell efficiency is affected by many factors, including surface morphology [ 34 , 35 ] or technical parameters of their preparation process [ 36 , 37 , 38 , 39 , 40 ]. It should be noted that the power conversion efficiency of OPV devices can be optimized by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The charge injection of polymer light-emitting diodes (PLEDs) is remarkably increased because ionic impurities in the polymer film can be oriented along the direction of the electric field [13]. Since then, EA has been applied to solution-processed organic diodes such as PLEDs, [14] organic photovoltaics (OPVs), [15]- [18] organic light-emitting diodes (OLEDs) with conjugated dendrimers, [19] organic salts, [20] and conducting polymer electrodes [21]. Researchers have suggested that ionic impurities in the organic layer migrate toward the electrodes owing to the electric field, leading to a reduction in the turn-on voltage.…”
Section: Introductionmentioning
confidence: 99%